The Court years, 1939-1975 : - Douglas, William O. (Random House, 1980)
This book is the personal record of Willliam O. Douglas's great lifelong struggle. Timely, newsworthy, historically important, The Court Years continues the memoirs Justice Douglas began so eloquently in his best selling Go East, Young Man